Basin futures, a novel cloud-based system for preliminary river basin modelling and planning. (July 2021) - Taylor, Peter; Rahman, Joel; O'Sullivan, Jackie; Podger, Geoff; Rosello, Caroline; Parashar, Amit; Sengupta, Ashmita; Perraud, Jean-Michel; Pollino, Carmel; Coombe, Mac
Abstract: Water resources are under growing pressure globally. Sustainable water management requires an understanding of how much water is available, where it is stored and used, and how future developments may impact availability. Understanding this requires investment in data, models, and experts. These investments are labour intensive, with considerable effort spent in three main areas: collecting and transforming data; building, calibrating, running and maintaining models; and developing required reports and visualisations. We present Basin Futures, a cloud-based product developed to lower this initial effort by providing pre-integrated data; a template model structure that makes some simplifying assumptions for speed; easy setup of new scenarios; a scalable data processing and simulation architecture; and delivery through a web browser. The case studies and results presented show the product is quick to learn, fast in execution, and provides an easy way to explore water resource development scenarios for river basin management and planning. Highlights: A new globally applicable, fast, easy to use, web-based system for preliminary water resources assessments at basin scale. Configurable scenarios for understanding impacts of water-resource developments and climate change. Extensive range of pre-integrated global hydrological and climate data sets. Innovative tool for web-based teaching of basin planning and water management. Requires no on-site installation or configuration.